Diary of the 1956 Hungarian Revolution in the Egyptian Government Press: يوميات ثورة المجر 1956 في الصحافة الحكومية المصرية - Abdel-Ati Al-Naggar, Abdallah (Études sur la Région Méditerranéenne, 2021)
During the summer and fall of 1956, the attention of the Egyptian and international public opinion and the political leadership was dominated by several exciting internal and external events: crises of financing the construction of the High Dam in Aswan, the nationalization of the Suez Canal Company, and the tripartite aggression against Egypt. However, these important events did not distract attention from the Egyptian press coverage of news and commentary related to the simultaneous Hungarian revolution. All contemporary Egyptian newspapers wrote about the situation in Hungary and followed the incoming news constantly, and even often published several news daily in this regard, which represented interest in the Hungarian issue. Recently, many studies on the echoes of the Hungarian Revolution of 1956 were released. In this article, I will focus primarily on how the Egyptian governmental newspapers dealt with the 1956 revolution. Among the Egyptian newspapers, I searched Al- Gomhoria, Al-Ahram, Akhbar Al-Youm. I chose these newspapers because they are the largest and most well-known daily newspapers in Egypt and the Arab world. All are daily newspapers with a great history and international reputation, and they deal with international news, especially political issues. These three newspapers are among the best Arab sources for true investigative journalism and objective political analysis. These newspapers address a large target audience, and their content is varied. These newspapers have published materials that are worthy of analysis on the Hungarian revolution by adopting three different methods of approaching.